Designing out crime in Western Australia: a systems approach to policy development - Cozens, Paul (Edith Cowan University: Security Research Centre 'SECAU', 2008)
Designing Out Crime is a system and a process for reducing both opportunities for crime and the fear of crime. These ideas, also known as crime prevention through environmental design (CPTED), form part of the Western Australian (WA) Government's Community Safety and Crime Prevention Strategy. Designing Out Crime is promoted by all other Australian States, as well as by the United Nations and the governments of North America, the UK, Europe, South Africa, Singapore, New Zealand and Chile among others. Internationally, although most countries provide some policy guidance on designing out crime, it is largely piecemeal, uncoordinated, fragmented and dispersed across many policy areas, initiatives and departmental agendas. WA?s Designing Out Crime Strategy (OCP, 2007) attempts to consolidate the multi-disciplinary and multi-agency dimensions and objectives of these ideas and adopted a systems approach to analysing and tackling this problem. The Designing Out Crime Strategy seeks to embed the ideas into relevant aspects of government policy, particularly the planning process. Essentially, it attempts to encourage policy-makers and practitioners to proactively ?think crime?, in designing all ?products? ? ranging from the design of cities, neighbourhoods and streets, to buildings and the spaces within them and ultimately to the ?products? which are placed within such spaces and bought and consumed by the community.